Local Expert Perceptions of Migration as a Climate Change Adaptation in Bangladesh - Stojanov, Robert; Kelman, Ilan; Ullah, A. K. M. Ahsan; Duží, Barbora; Procházka, David; Kavanová Blahůtová, Klára (MDPI AG, 2016)
People have long migrated for many reasons, often with a combination of forced and voluntary reasons combining to push them away from current situations and to pull them towards new situations. Bangladesh is one example where environmental changes have long been amongst the multitude of reasons for migrating, with contemporary climate change suggested as a major impetus towards more migration. This paper examines local expert perceptions of migration as a climate change adaptation strategy for Bangladeshis. Seventeen in-depth interviews were conducted with local experts in Bangladesh and Assam (India) on environmental change and migration to understand the perspectives of those with formal education and expert-related jobs who come from the areas being directly affected by Bangladeshi migration. Findings show that local experts consider that migration is used and will be used for climate change adaptation in Bangladesh, but migration is not solely for climate change adaptation, instead interweaving with all other factors influencing migration-related decisions.
Keywords: adaptation; Bangladesh; climate change; climate migration; environmental migration; India; migrants